The Influence of Using Talking Stick Technique to the Speaking Ability of Eleventh Grade Students at SMAN 1 GondangNganjuk - Sari, Widiya (Universitas Nusantara PGRI Kediri, 2016)
The aims of this research were to find out there was a significant influence of students’ speaking ability before and after being taught use talking stick technique. The sample of this research was class XI IPS 4 of the second grade at SMAN 1 GondangNganjuk in the academic year 2014/2015. The research applied one group pre-test post-test design. The result of the speaking ability by using talking stick technique type of cooperative learning showed that there was a significant influence on students’ speaking ability. The average of post-test score (73.25) was higher than that of pre-test (50.52), and it has gain 22.73. It means that there is an influence of using talking stick technique to the speaking ability of eleventh grade students at SMAN 1 GondangNganjuk in academic year 2014/2015.